KONFLIK SOSIAL BERBASIS COVID-19 DALAM PERSPEKTIF TEORI SOSIAL SOCIAL CONFLICT BASED ON COVID-19 IN SOCIAL THEORY PERSPECTIVE - Abubakar M Nur (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2021)
The emergence of a phenomenon in the public space that has the potential for conflict, because there are those who act as facelessmovement actors who have networks or networks, which are used as sources of social action. An action is called a social action, because thesubjective meaning is associated with individuals who act and take into account the behavior of others. Humans are actors who try to combinepersonal characteristics that are addressed to others. The purpose of this research is to find out and understand the background of Social Conflictbased on the Covid-19 Phenomenon, in the perspective of Social Action theory and Dramaturgy Theory. This study uses a qualitative approach.Data was collected through tracking information from various social media, and related documents and literature studies relevant to thisresearch. This study shows that social conflicts are caused by misunderstandings, both the community and the government inaddressing the issue of the COVID-19 pandemic, which is broadcast through social media, as hoaxes or as social facts. The government'sinability to provide public comfort from the issue of the COVID-19 pandemic, in the digital era. The government's thinking structure andpolicies have been infected with the manifest interests of power.Lockdown cannot be carried out because of the consequences for Covid- 19 exporting countries, not being able to freely enter certain areas inIndonesia. There are certain actors who have succeeded in using the social media space to produce public panic. Massive panic occurs in thecommunity which has an impact on the emergence of weak mental illnesses that directly affect humans, so they are powerless to doanything.